How to cope in heterogeneous coastal environments: Spatio-temporally endogenous circadian rhythm of valve gaping by mussels - Bertolini, C.; Rubinetti, S.; Umgiesser, G.; Witbaard, R.; Bouma, T.J.; Rubino, A.; Pastres, R. (The Science of the total environment, 2021)
Transitional coastal zones are subject to high degrees of temporal fluctuation in environmental conditions, with these patterns varying in space. Gaining an in depth understanding of how sessile organisms cope with and respond to such environmental changes at multiple scales is needed to i) advance fundamental knowledge, ii) predict how organisms may react to stressors and iii) support the management of halieutic resources in transitional coastal areas. We addressed this question using mussels (Mytilus galloprovincialis) as model system. Valve-gaping sensor were deployed at multiple sites within the southern Venice Lagoon over a period of 6 months, to investigate the existence of periodicity in valve-gaping and its relationship with environmental variables, such as temperature and chlorophyll-a. Gaping behaviour was found to have periodic rhythms, of ~12 h and ~ 24 h, which were most pronounced in the inner part of lagoon part and were strongest during summer months. In autumn, the dual periodicity became weaker and mostly the 12 h remained. Gaping was closely linked with tide, but the relationship in terms of phasing varied upon location. Surprisingly, no clear direct relationships were found with chlorophyll-a, but food delivery may be mediated by tide itself. The results highlight the heterogeneity of behaviour and the endogenic nature of circadian rhythms in space and time. These findings have important implications for management of transitional areas where tidal alteration may have impacts on key behaviours, and emphasize the importance of characterizing their rhythms before using these as stress indicator. Moreover, the described tidal relationships should be included in growth models of bivalves in these systems. [Display omitted] •It is necessary to understand how organisms respond to environmental changes.•Transitional coastal areas are great model systems.•Mussels behaviour was monitored long-term and in continuous in three sites.•It followed the tidal rhythm particularly in more internal site and in summer.•Responses to small scale changes are important for management and for predictions.